Managing a Mass CO Poisoning: Critical Issues and Solutions From the Field to the Hyperbaric Chamber. (4th July 2016) - Valerio, Adriano; Verzè, Matteo; Marchiori, Francesco; Rucci, Igor; De Santis, Lucia; Aprili, Irene; Antolini, Lucia; Sannino, Anna; Canello, Alessia; Checchin, Enrico; Mazzola, Francesca; Ferrari, Sara; et al.
Abstract: Carbon monoxide acute intoxication is a common cause of accidental poisoning in industrialized countries and sometimes it produces a real mass casualty incident. The incident described here occurred in a church in the province of Verona, when a group of people was exposed to carbon monoxide due to a heating system malfunction. Fifty-seven people went to the Emergency Department. The mean carboxyhemoglobin (COHb) level was 10.1±5.7% (range: 3-25%). The clinicians, after medical examination, decided to move 37 patients to hyperbaric chambers for hyperbaric oxygen (HBO) therapy. This is the first case report that highlights and analyses the logistic difficulties of managing a mass carbon monoxide poisoning in different health care settings, with a high influx of patients in an Emergency Department and a complex liaison between emergency services. This article shows how it is possible to manage a complex situation with good outcome. ( Disaster Med Public Health Preparedness . 2017;11:251–255)